2012
DOI: 10.1021/jm2014887
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of (S)-6-(3-Cyclopentyl-2-(4-(trifluoromethyl)-1H-imidazol-1-yl)propanamido)nicotinic Acid as a Hepatoselective Glucokinase Activator Clinical Candidate for Treating Type 2 Diabetes Mellitus

Abstract: Glucokinase is a key regulator of glucose homeostasis, and small molecule allosteric activators of this enzyme represent a promising opportunity for the treatment of type 2 diabetes. Systemically acting glucokinase activators (liver and pancreas) have been reported to be efficacious but in many cases present hypoglycaemia risk due to activation of the enzyme at low glucose levels in the pancreas, leading to inappropriately excessive insulin secretion. It was therefore postulated that a liver selective activato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
107
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(113 citation statements)
references
References 59 publications
(76 reference statements)
5
107
0
Order By: Relevance
“…However, GKAs may cause serious side effects, as they change a sigmoidal activity curve of GK into a hyperbolic one (8,9), and consequently alter the sensing of blood glucose level by GK in pancreatic β-cells, resulting in hyperinsulinemic hypoglycemia. As an approach to avoid the side effect, moderate or hepatocyte-specific GKAs are under development (36)(37)(38). With the same rationale and based on our result, GKRP can be a target for the development of new antidiabetes drugs that activate GK in hepatocytes.…”
Section: Discussionmentioning
confidence: 77%
“…However, GKAs may cause serious side effects, as they change a sigmoidal activity curve of GK into a hyperbolic one (8,9), and consequently alter the sensing of blood glucose level by GK in pancreatic β-cells, resulting in hyperinsulinemic hypoglycemia. As an approach to avoid the side effect, moderate or hepatocyte-specific GKAs are under development (36)(37)(38). With the same rationale and based on our result, GKRP can be a target for the development of new antidiabetes drugs that activate GK in hepatocytes.…”
Section: Discussionmentioning
confidence: 77%
“…Thus, medicinal chemists have become more proficient in designing metabolically stable compounds (5,6). Plus, new targets, structure classes, and dosing paradigms are being explored, such as liver targeting (7)(8)(9) and once weekly dosing (10). All these strategies need to drive the clearance very low.…”
Section: Introductionmentioning
confidence: 99%
“…1), with preferential GK activation in hepatocytes versus pancreatic b-cells (Pfefferkorn et al, 2012). GK is a glycolytic enzyme that catalyzes the phosphorylation of glucose to glucose-6-phosphate (Mithieux, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In preclinical animal models of diabetes, PF-04991532 was found to robustly lower fasting and postprandial glucose and was devoid of hypoglycemic risks, leading to its selection as a clinical candidate for treating T2DM. The in vivo pharmacokinetics of PF-04991532 were characterized by high systemic plasma clearance (CL p ) values of 51 and 35 ml/min per kg in rats and dogs, respectively, and oral bioavailability of ;18% in both rats and dogs (Pfefferkorn et al, 2012). Resistance of PF-04991532 to metabolic turnover in liver microsomes and hepatocytes from a rat, dog, and human suggested that metabolic elimination would be inconsequential as a clearance mechanism in vivo.…”
Section: Introductionmentioning
confidence: 99%